The Scandinavian Model in Healthcare and Higher Education:: Recentralising, Decentralising or Both? - Torjesen, Dag Olaf; Foss Hansen, Hanne; Pinheiro, Rómulo; Vrangbæk, Karsten (Scandinavian Journal of Public Administration, 2017)
The public sector in the Nordic countries has been subject to substantial reform in recent decades. The article explores the changing reform dynamic in Denmark and Norway, focusing on centralising and decentralising trends in two prominent sectors: higher education and health care. The main question is: How can the reform dynamics over the last decade explain changes surrounding decentralisation and/or re-centralisation? A new trend can be observed in both sectors, namely the rise of re-centralisation and the concomitant growth of state responsibility in matters pertaining to political and fiscal decision-making. Both hospitals and universities have been given increased (procedural) autonomy. At the same time there is stronger centralised planning and management of performance management, which means that (substantive) autonomy has been reduced.